THE EVOLUTION OF BELARUSIANS FUNERAL AND COMMEMORIAL CEREMONIES IN XX – THE BEGINNING OF XXI CENTURY (BASED ON THE MATERIALS OF THE BELARUSIAN PODVINIYE) (Philological Studies, 2019)
The paper traces the evolution of the funeral and memorial rites of Belarusians in the XX – early XXI centuries on the basis of the materials of the Belarusian Podviniye. The research data is folklore and ethnographic materials, some information was recorded by the author. The research shows the dynamics, reveals the main change direction of funeral and memorial rites, and characterizes its state. The contemporary funeral and memorial rites include traditional and new elements, which are revealed and described in the article.
Keywords: evolution, funeral rites, Belarusian ethnos, Podviniye, burial, commemoration, traditional culture.